2016
DOI: 10.1159/000452358
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Trisomy 8 Mosaicism with Persistent Macrocytosis

Abstract: Constitutional trisomy 8 mosaicism (CT8M) is a rare chromosomal abnormality. The phenotype varies from normal features to severe malformations. CT8M increases the risk of developing leukemia and myelodysplastic syndrome. As CT8M is very rare, its diagnosis can easily be overlooked, especially in cases with mild phenotypes. Here, we report the diagnostic process of a 40-year-old female patient with CT8M and discuss the importance of follow-up in monitoring for hematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Around 80% of germline GATA2 carriers develop a myeloid malignancy before the age of 40 years ( 40 ), and it is shown that the progression to malignancy can occur through multi-step secondary events targeting various hematopoietic pathways. These include (but are not limited to) acquired biallelic mutations in CEBPA ( 41 , 42 ) which lead to differentiation blocks in some AML subtypes ( 38 ), NRAS, ASXL1, SETBP1, NPM1, and WT1 secondary mutations ( 43 ), chromosomal abnormalities (monosomy 7 or trisomy 8) ( 44 )), disrupting the regeneration abilities of enhancers ( 45 ), HSC exhaustion following repeated infections, and changes in DNA binding affinities that result in disruptions to interaction partners/target genes. ( Figure 1 ) For example, the GATA2 p.T354M missense variant may contribute to the leukemogenic process in two ways, by partial loss of GATA2 transactivation activity and simultaneous increased affinity to PU.1 ( 46 ), thereby potentially interfering with differentiation and driving cells towards granulocytic disease ( 7 ).…”
Section: Oncogenic Tf Network In Hematopoiesismentioning
confidence: 99%
“…Around 80% of germline GATA2 carriers develop a myeloid malignancy before the age of 40 years ( 40 ), and it is shown that the progression to malignancy can occur through multi-step secondary events targeting various hematopoietic pathways. These include (but are not limited to) acquired biallelic mutations in CEBPA ( 41 , 42 ) which lead to differentiation blocks in some AML subtypes ( 38 ), NRAS, ASXL1, SETBP1, NPM1, and WT1 secondary mutations ( 43 ), chromosomal abnormalities (monosomy 7 or trisomy 8) ( 44 )), disrupting the regeneration abilities of enhancers ( 45 ), HSC exhaustion following repeated infections, and changes in DNA binding affinities that result in disruptions to interaction partners/target genes. ( Figure 1 ) For example, the GATA2 p.T354M missense variant may contribute to the leukemogenic process in two ways, by partial loss of GATA2 transactivation activity and simultaneous increased affinity to PU.1 ( 46 ), thereby potentially interfering with differentiation and driving cells towards granulocytic disease ( 7 ).…”
Section: Oncogenic Tf Network In Hematopoiesismentioning
confidence: 99%